G-6PD Screening in Neonatal Hyperbilirubinemia - Suvitha Thilakarajan; S.R Niveditha; Keshavamurthy (JCDR Research and Publications Pvt. Ltd., 2015)
Glucose-6-Phosphate Dehydrogenase deficiency (G6PDD), is one of the commonest X-linked inherited erythroenzymopathy affecting 10% of the world population with a frequency of 0-27% in India. Children with G6PDD can develop acute haemolytic crises precipitated by particular foods or drugs causing significant morbidity. As primary prevention is not available, the only way to avoid morbidity is to recognize such children early in life and prevent exposure to triggering agents and drugs. Aims/ Objectives: 1. To screen and determine the frequency of G6PDD in cases of neonatal hyperbilirubinemia ( > 12.9 mg/dl). 2. To assess the usefulness of methaemoglobin reduction (MR) test in neonatal screening for G6PDD. Results: This observational study conducted in the department of pathology, at Kempegowda Institute of Medical Sciences, Bengaluru included 310 neonates with hyperbilirubinemia (12.9gm%). The male: female ratio was 1.3:1 with 80.3% of neonates presenting between 3-5 days post-birth with jaundice. Majority of the neonates were from non-consanguineous marriages (91.65%). Birth weight of 83.7% of the neonates was found to be > 2.5 kgs. Frequency of G6PDD was 1% ( 3 females) by MR test. All the G6PD deficient neonates (3/310 cases) were females (P=0.045), from non-consanguineous marriages. Conclusion: Frequency of G6PDD in neonatal hyperbilirubinemia was 1% (3/310 cases) suggesting low prevalence in south India. MR test appeared to be a good screening test as it was effective in picking up heterozygotes (all three were females, P=0.045).